Penerapan Model Project Citizen dalam Upaya Meningkatkan Kecerdasan Ekologis - Rahayu, Galih Dani Septiyan; Setiyadi, Ruli (Mimbar Sekolah Dasar, 2018)
This research is an effort to improve ecological intelligence by using the Citizen project model. The method used in this study was a classroom action research in which regular 3rd semester students of Elementary School Teacher Education (IKIP) Siliwangi were the subject. The result of this research showed that the teaching plan through the citizen project model needs careful planning. There are some obstacles in implementing the above model i.e. students are still rigid in finding the problems, making solutions to problems and solving problems. Nevertheless, through the improvement in subsequent cycles, the better ecological intelligence can be seen from cycle I to cycle III in the aspect of knowledge with an average score of 86 (excellent), awareness 3.60 (excellent) and the application 3.70 (very good). The above scores improvement is associated with the ecological intelligence aspects of waste care.